Determinants of public engagement on municipal Facebook pages. Issue 3 (26th May 2020) - Metallo, Concetta; Gesuele, Benedetta; Guillamón, María-Dolores; Ríos, Ana-María
Abstract: This article analyzes the determinants of public engagement on the Facebook pages of municipalities. The sample consists of 170 Italian and Spanish municipalities that used Facebook in 2014. The findings show that posting a lot of information on municipal Facebook pages does not increase the engagement of citizens. Also, frequent posting of information per se does not engage public engagement. However, if the posts are published when public can pay attention to them (e.g., off days), the likelihood of public engagement increases. Furthermore, the citizens' engagement on municipal Facebook page depends on the level of citizens' income – there is a negative relationship between citizens' income and the level of participation.